Gender political inclusion and inclusive finance in Africa - Tii Njivukuh Nchofoung; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
At the 2010 G20 Summit, the use of formal financial services was recognized as one of the main pillars of the global development agenda. At the same time, the fifth goal of the Sustainable development agenda outlined the importance of gender inclusion for sustainable development. Empirical research on the effect of gender inclusion on inclusive finance has however been limited to micro level studies. This study aims to verify the effect of gender political inclusion on financial inclusion on a sample of 37 African countries from 2004- 2020. The empirical methodology involves the Ordinary Least Squares (OLS), the Tobit regression and the System Generalized Method of Moments (GMM) methodologies. The results from these methods show that gender political inclusion is enhancing on financial inclusion in Africa, and this finding is robust across alternative specifications of gender inclusion and inclusive finance. Besides, governance exhibits a positive synergy effect with gender political inclusion on inclusive finance. Policy implications are discussed.
Keywords: G20; I32; O55; P16; P43; 330; Gender; political inclusion; inclusive finance; Africa